Pencampuran Tepung Okra Hijau (Abelmuschus esculentum L.) pada Pembuatan Mie Basah Ditinjau dari Sifat Organoleptik dan Kadar Serat Pangan - Agustiana Agustiana; Waluyo Waluyo; Fery Lusviana Widiany (Jurnal Gizi, 2020)
Noodle is a form of processed food from wheat flour that is widely consumed and preferably bye the community. Abelmuschus was underutillized food while they do have high content of fiber. The use of green okra flour as the flour mixture in the manufacture of wet noodles was expected to create a new noodle product that has high fiber content. This study was to determine the effect of green okra flour of wet noodle on organoleptic characteristics, and dietary fiber content. This was a true experimental study with complete random design. The independent variable was substitution of green okra (Abelmuschus esculentum l.) flour on wet noodle, while the dependent variables were organoleptic characteristics and dietary fiber value. There were four variations of wet noodles i.e. 0%, 10%, 15%, and 20%. data were analyzed using Kruskal-wallis, Mann Whitney test and Anova. The result showed wet noodle 10% was whitish green, typical flavour of wet noodle, and has a chewy on texure.the highes levels of dietary fiber content was ini wet noodle 20% asa many as 9,92 grams. In conclusion, there are significant differences in organoleptic test results based on aroma and taste, but there are no differences based on color and texture. There were significant differences in dietary fiber content from the four experiment variations. The greater the percentage of mixing green okra flour, the fiber content will be higher in wet noodles.